Validation of Combined Transport Quality Criteria - Brnjac, Nikolina; Jolić, Natalija; Jenić, Vinko (Promet - Traffic&Transportation, 2006)
With the globalization of market the production processand the life-cycle of the products have shortened by increasingthe expectations of industry for ’’iust-in-time’ logistic solutions.At the same time the competition on the global markets has increasedthe number of ’players’ and the objectives of purchaseand distribution chains. The objective is to develop the framefor optimal integration of different transport modes thus facilitatingmaximally efficient and cost-effective usage of the transportsystem through user-oriented ’door-to-door’ transportand to stimulate by this service the competition among transportoperators.